2019
DOI: 10.1101/602722
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neutrophil Extracellular Traps contribute to the pathogenesis of leprosy type 2 reactions

Abstract: 25Up to 50% of patients with the multibacillary form of leprosy is expected to 26 develop acute systemic inflammatory episodes known as type 2 reactions (T2R), 27 thus aggravating their clinical status. Thalidomide rapidly improves T2R 28 symptoms. But, due to its restricted use worldwide, novel alternative therapies 29 are urgently needed. A hallmark of T2R lesions is the presence of a neutrophil-30 rich inflammatory infiltrate. In this study, the potential involvement of neutrophil 31 extracellular traps (NE… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…15,19,20 Recent studies have focused on the role of neutrophil DNA extracellular traps (NET), and there is good data to show that thalidomide has an inhibitory action on NET. 21 In addition thalidomide effectively decreases the activated low-density neutrophils, increases the level of TGF-b, an inhibitor of neutrophilic degranulation, and also decreases MMP-9 serum levels. 22 The dramatic reduction in neutrophilic infiltrate within 7 days of thalidomide induction lends further support to this view 23 (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15,19,20 Recent studies have focused on the role of neutrophil DNA extracellular traps (NET), and there is good data to show that thalidomide has an inhibitory action on NET. 21 In addition thalidomide effectively decreases the activated low-density neutrophils, increases the level of TGF-b, an inhibitor of neutrophilic degranulation, and also decreases MMP-9 serum levels. 22 The dramatic reduction in neutrophilic infiltrate within 7 days of thalidomide induction lends further support to this view 23 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Thalidomide treatment reduces CD64 expression and neutrophil infiltration and suppresses IL‐1β as well as IL‐10R1, which stimulates neutrophils 15,19,20 . Recent studies have focused on the role of neutrophil DNA extracellular traps (NET), and there is good data to show that thalidomide has an inhibitory action on NET 21 . In addition thalidomide effectively decreases the activated low‐density neutrophils, increases the level of TGF‐β, an inhibitor of neutrophilic degranulation, and also decreases MMP‐9 serum levels 22 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that dead Mycobacterium leprae have a superior capacity to induce CCL-4 and IL-8 in primary neutrophils, which elegantly explains the fact that dead M. leprae mediate ENL. 13 A recent study has also found that neutrophil DNA extracellular traps also play a role in ENL, 14 and there are data to show that thalidomide has a inhibitory action on neutrophils, thus making it an effective drug in ENL. The dramatic reduction in neutrophilic infiltrate within 7 days of thalidomide induction lends further support to this view.…”
Section: Discussionmentioning
confidence: 99%
“…The commonality among the patients with ENL and COVID-19 is the presence of neutrophilia and high NLR (22). One study showed the presence of circulating and skin-lesion neutrophil releasing NET along with higher DNA-histone serum levels upon comparison with non-reactive multibacillary controls (23). From a clinical perspective, COVID-19 and ENL differ, however, their transcriptome profiling and neutrophil activation are similar.…”
Section: Do Corticosteroids Exacerbate Severity In Leprosy Patients?mentioning
confidence: 99%